Dysregulation of hypothalamic‐pituitary estrogen receptor α–mediated signaling causes episodic LH secretion and cystic ovary. Issue 6 (13th March 2019) - Arao, Yukitomo; Hamilton, Katherine J.; Wu, San-Pin; Tsai, Ming-Jer; Demayo, Francesco J.; Korach, Kenneth S.
ABSTRACT: Polycystic ovary syndrome (PCOS) is a hypothalamic‐pituitary‐gonadal (HPG) axis disorder. PCOS symptoms most likely result from a disturbance in the complex feedback regulation system of the HPG axis, which involves gonadotrophic hormones and ovarian steroid hormones. However, the nature of this complex and interconnecting feedback regulation makes it difficult to dissect the molecular mechanisms responsible for PCOS phenotypes. Global estrogen receptor α (ERα) knockout (KO) mice exhibit a disruption of the HPG axis, resulting in hormonal dysregulation in which female ERt* KO mice have elevated levels of serum estradiol (E2), testosterone, and LH. The ERt* KO females are anovulatory and develop cystic hemorrhagic ovaries that are thought to be due to persistently high circulating levels of LH from the pituitary. However, the role of ERt* in the pituitary is still controversial because of the varied phenotypes reported in pituitary‐specific ERα KO mouse models. Therefore, we developed a mouse model where ERt* is reintroduced to be exclusively expressed in the pituitary on the background of a global ERα‐null (PitERtgKO) mouse. Serum E2 and LH levels were normalized in PitERtgKO females and were comparable to wild‐type serum levels. However, the ovaries of PitERtgKO adult mice displayed a more overt cystic and hemorrhagic phenotype when compared with ERt* KO littermates. We determined that anomalous sporadic LH secretion caused the severe ovarian phenotype of PitERtgKO females. Our observations suggest that pituitary ERα is involved in the estrogen negative feedback regulation, whereas hypothalamic ERt* is necessary for the precise control of LH secretion. Uncontrolled, irregular LH secretion may be the root cause of the cystic ovarian phenotype with similarities to PCOS.—Arao, Y., Hamilton, K. J., Wu, S.‐P., Tsai, M.‐J., DeMayo, F. J., Korach, K. S. Dysregulation of hypothalamic‐pituitary estrogen receptor α–mediated signaling causes episodic LH secretion and cystic ovary. FASEB J. 33, 7375–7386 (2019). www.fasebj.org